Difference between bio-plastic production from com starch and fish Scales and bio-plastic production from corn starch, fish scale and coconut fibers / Nazatul Dayana Ahmad Rashidi ...[et al.] - Ahmad Rashidi, Nazatul Dayana; Zamran, Nor Aifa Nabilah; Shaiful Izam, Shamira; Muhammad, Arbanah
The aim of this study is to evaluate the mechanical properties and the water absorption of bio-plastic made from corn starch, fish scale and bio-plastic made from corn starch, fish scale and coconut fibers. The objective of additional coconut fibers to the bio-plastic is to reinforce the bio-plastic but it has some drawback as it is relatively high moisture absorption. Water absorption test and tensile test were employed to prove the presence study. It was found that the percentage of water absorption for the bio-plastic that contain coconut fiber has higher percentage of water absorption which up to 30%. While the tensile test shows that the maximum tensile strength is up to 0.22265 N/mm2 if the bioplastic is added with coconut fiber. The elongation-to-break shows the decrease of elongation when added with coconut fiber. Ultimately, this paper shows that the addition of natural fibers in the bio plastic increases the tensile strength and also the water absorption.